Asthma and the Olympics - Carlsen, K.-H.; Lødrup Carlsen, K. C. (The Journal of Allergy and Clinical Immunology, 2016)
Pierre de Coubertin, the first president of the International Olympic Committee, chose "Citius, Altius, Fortius" ("Faster, Higher, Stronger") as the Olympic motto in 1894. Today, this motto, stating the need for continuous improvement in physical performance, should also be considered from the perspective of the increase in asthma prevalence among elite athletes that has occurred in recent decades. Asthma is presently the most common chronic condition found among elite athletes participating in the Olympic Games.